KINERJA KOMPUTASI TERDISTRIBUSI BERBASIS LAYANAN WEB MENGGUNAKAN METODE SOAP SIMPLE OBJECT ACCESS PROTOCOL - Yogiswara Yogiswara (Jurusan Teknologi Informasi Politeknik Negeri Jember, 2019)
Technology web services (Web Service) published to overcome the problems interoperabillitas between applications is a major obstacle in the process of data integration. This technology is a distributed computing technology that is widely used because of its simplicity and flexibility than previous technologies. There are three methods of data exchange which has been standardized in this technology, one of which is a SOAP (Simple Object Access Protocol) is a protocol for the exchange of information with a remote procedure call mechanism through HTTP protocol in the form of XML. These methods has been widely applied in many cases but still have not measured the performance of this method, especially in the execution of data. In this study, the method of exchan ge of SOAP tested its performance in a distributed environment with different server platforms. Performance measurement results show the method has the SOAP protocol that is easy to understand by the client for the service descriptions using the standard WSDL (web services description language), while a web server that has the best performance in executing SOAP is a web server NGINX